2024
DOI: 10.1037/qup0000280
|View full text |Cite
|
Sign up to set email alerts
|

The role of gender in career satisfaction for female surgeons.

Leeat Granek,
David J. Barron,
Abhaya V. Kulkarni
et al.

Abstract: Despite working many hours under stressful conditions, surgeons report high levels of career satisfaction. However, female surgeons report lower career satisfaction and are underrepresented in some surgical fields. The goal of this analysis was to explore how gender influences career satisfaction for pediatric surgeons working in male-dominated subspecialties using a qualitative approach to inquiry. The grounded theory method of data collection and analysis was used. Forty-two surgeons from nine countries were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…These are concerning responses given the enormous body of literature on discrimination against women in surgery. 1,[18][19][20]22,23,26,[34][35][36][37][38][39][40][41][42] With so much accumulating evidence documenting these inequities, we expect there to be a higher awareness among all surgeons in recognizing discrimination. Of note, our study revealed that women did have a keener awareness of racial discrimination than men, even if they did not experience it firsthand.…”
Section: Discussionmentioning
confidence: 99%
“…These are concerning responses given the enormous body of literature on discrimination against women in surgery. 1,[18][19][20]22,23,26,[34][35][36][37][38][39][40][41][42] With so much accumulating evidence documenting these inequities, we expect there to be a higher awareness among all surgeons in recognizing discrimination. Of note, our study revealed that women did have a keener awareness of racial discrimination than men, even if they did not experience it firsthand.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, Granek et al (2024) provide an exemplar of this form of research in their study of female surgeons. She uncovers and explores the paradox of these women reporting that they did not experience gender bias, while also reporting instances in which discrimination was evident.…”
Section: The Continued Necessity Of Qualitative Methods Activismmentioning
confidence: 99%